Money and Body for Male’s Pleasure: A Psychoanalytical Reading of Ernest Hemingway’s A Farewell to Arms - Shahi, Ashok Kumar (The Outlook: Journal of English Studies, 2020)
This article explores World War I Hero, Expatriates: Money and Body are two major objects for males’ pleasure. The very title is slightly discussed applying psychoanalytical approach. Mainly, it studies focusing on Freudian and Jungian concepts of Sex and Sexuality. Statement of problems is to find out what made the people go outside the country as expatriates mainly to the protagonist Lieutenant Frederic Henry and Catherine Barkley, in the novel A Farewell to Arms, written by Ernest Hemingway. Furthermore, this article tries to analyze World War I Hero and Expatriates: Money and Body for Male’s pleasure with reference to some critics in the body part of this article. In A Farewell to Arms, the hero, Frederic Henry, is badly injured by the bomb shell in the Italian front during the World War I. He is admitted to the Milan hospital and has been involved with the nurse Catherine Barkley. She is a volunteer nurse and the central character. However, the hero, Henry is attracted towards her for his pleasure not only from the perspective of money but for body and pleasure. These two characters represent the American and British expatriates who are crowding the bars, restaurants, night clubs, bull fight sports or in different entertaining places getting fed up with the horrors of World War I. They live comfortably in the foreign country. They want to get rid of the war and weapons so that they can enjoy as outsiders in the foreign countries as expatriates.